(untitled) (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
The Covid-19 pandemic has affected various aspects. At least, with the role of technology it is still possible to do online learning. English, as one of the most widely spoken languages and thus being the most studied in many countries, is automatically one of the most important languages to learn. With the pandemic that reduces social interaction and the quality of direct communication. The studentsÃ¢â‚¬â„¢ enthusiasm in learning English decreases because learning is no longer fun and attractive. In fact, at SMAN 1 Jalancagak which is the place where the researcher conducted observations. The researcher found a lot of students’ behavior which showed how unenthusiastic they were in learning English. They issue various excuses to the teacher while teaching to avoid English lesson. Therefore, researchers are interested in analyzing the phenomenon of student enthusiasm after the pandemic at SMAN 1 Jalancagak. So this research is called "Analysis of Student’s Enthusiasm in Learning English after the COVID-19 Pandemic at the Eleventh grade Students of SMAN 1 Jalancagak Academic Year 2021/2022". Researchers in this study used a qualitative research design. Researchers used several instruments to support this research, including: Observations, interviews, and recordings. With this research, the researcher hopes that the results of this study can become data and references that can be used as discussion material for other researchers and teachers about how to maintain the enthusiasm of students.